Analisis Pendapatan Usahatani Labu Siam Di Desa Harusan Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara Propinsi Kalimantan Selatan - Muhammad Haris (Rawa Sains: Jurnal Sains STIPER Amuntai, 2012)
Agricultural development aims to increase agricultural production to meet the food needs and needs of the domestic industry, increase exports, increase farmer incomes, expand employment opportunities and support opportunities. Vegetable production in North Hulu Sungai is very diverse, such as pumpkin or known as pumpkin. This study aims to (i) find out the total costs, income and income obtained by farmers from side farming in Harusan Village, (ii) find out the side farms that provide the largest farmers' income in Harusan Village. The study began from May - August 2011, namely from preparation to preparation of reports. The type of data collected in this study consists of primary data and secondary data. Sampling for farmers is all farmers who produce Alabio pumpkins and yams in Harusan Village, Central Amuntai District. From a total population of 78 farmers who planted squash by-products spread in Harusan Village, they were taken randomly using purposive random sampling method. The total cost of an average pumpkin is Rp. 936,600.39, - The average receipt of farmer's pumpkin is Rp. 1,466,111.11, -. The average income of pumpkin farmers is Rp. 1,381,791.67, -. Farmers who plant pumpkins in Harusan Village provide a large income for farmers